Penerapan Isometric Handgrip Exercise terhadap Tekanan Darah pada Penderita Hipertensi - Geby Natasya Br Butar Butar; Sri Indaryati; Sanny Frisca (Inovasi Kesehatan Global, 2026)
Hypertension is one of the major noncommunicable diseases and a significant global health problem due to its increasing prevalence and its risk of causing cardiovascular disease, stroke, kidney failure, and premature death. Blood pressure control can be achieved through pharmacological and nonpharmacological therapies, one of which is Isometric Handgrip Exercise (IHE), a static contraction exercise using a handgrip device that may improve vascular function and reduce blood pressure. This study aimed to implement IHE to reduce blood pressure in patients with hypertension. A case study design using an Evidence-Based Nursing Practice (EBNP) approach was conducted involving three patients with hypertension. IHE was administered once daily for three consecutive days, with each session lasting 14 minutes. Blood pressure was measured before and after the intervention using a sphygmomanometer. The results showed a mean reduction in systolic blood pressure of 10.67 mmHg and diastolic blood pressure of 6.67 mmHg. Patients also reported feeling more relaxed and experiencing reduced hand stiffness. The implementation of IHE may help lower blood pressure and can be used as a simple, safe, and easily applicable nonpharmacological nursing intervention.